Correlation between Seasons and the Prevalence of Preeclampsia at Tertiary Hospital, Indonesia - Monika Lijuwardi1, Budi Prasetyo1 , Muhammad Ardian Cahya Laksana1 , Rizki Pranadyan1 , Hanifa Erlin (Indian Journal of Forensic Medicine & Toxicology, 2020)
Background: Preeclampsia is the second most common cause of maternal mortality following postpartumhemorrhage. In East Java alone the maternal mortality rate due to preeclampsia was 31%. Some studiesexplain that the incidence of preeclampsia can be caused by seasonal variations, whereas other studies saythat seasonal factors can be a protective factor for preeclampsia.Objective: To find out how seasons relate to the prevalence of preeclampsia.Method: A descriptive analytic study using medical record data during. The sample meets the inclusioncriteria, namely pregnant women with preeclampsia, severe preeclampsia, chronic hypertension withsuperimposed severe preeclampsia, or eclampsia. The exclusion criteria were pregnant women with chronichypertension or gestational hypertension. The sampling technique used was total sampling and crosssectional design with observation method using secondary data from medical records. Data was processedusing IBM SPSS Statistics and presented narratively.Results: Respondents who experienced preeclampsia in the dry season were 558 people or 19.3% and thosewho did not experience preeclampsia were 844 people or 29.2% The results of data analysis with statisticaltests using Chi-Square obtained a significance value or p-value of 0.091 (p> 0.05).Conclusion: No correlation between seasonality and the prevalence of preeclampsia.